Antioxidant Activity and Phytochemical Content of Clerodendrum serratum L. from Different Provinces of Chhattisgarh State, India - Upadhyay, Seema; Koche, Vijaya (Asian Journal of Chemistry, 2019)
Clerodendrum serratum L. is one of the important medicinal plant found in Chhattisgarh state of India. Its over-exploitation for medicinal value made it a threatened species according to Chhattisgarh Medicinal Plant Board. It is being used in Ayurveda from ancient times for many diseases like asthma, body ache, bronchitis, cholera, dropsy, eye diseases, fever, inflammations, malaria, ophthalmia, rheumatism, snakebite, tuberculosis, ulcers and wounds. Present study aimed to compare the phytochemical contents and antioxidant activity of a medicinally important plant C. serratum L. collected from different provinces of Chhattisgarh state (India). Plants were collected from three districts of Chhattisgarh (Jagdalpur, Bilaspur and Raipur). Aerial and underground parts were separated and subjected for extraction by using different solvents of different polarity. These extracts were evaluated for phytochemical profiling, phytochemical content (total phenolic and flavonoids content) and antioxidant activity. Methanolic extract shows highest antioxidant activity and phenolic and flavonoids content among all the extracts. When the plants of different regions were compared, it was found that plants of Jagdalpur district is a potent source of phytochemical and showing highest antioxidant activity. Further, the correlation study showed that phenolics and flavonoids mainly account for antioxidant activity. It may be possible that some different groups of phytochemical act synergistically together with the phenolics and flavonoids and provide antioxidant effect.